STUDI TINGKAT BAHAYA BANJIR DAS BATANG KURANJI KECAMATAN PAUH KOTA PADANG - Nina Ismayani (Jurnal Azimut, 2020)
High rainfall with human factor make happen change characteristic especially at upper zone cause batang Kuranji stream. This research was conducted with the aim of 1) determine the characteristics of land Batang Kuranji Pauh sub district 2) determine the level of flood hazard Batang Kuranji Pauh sub district 3) analyze the spatial distribution of flood hazard Watershed (DAS) Batang Kuranji Pauh sub district. The results showed that: 1) there are differences in the characteristics of the land (land form, slope of land, damming of river, river meanders, the average slope of the watershed, land use, rainfall, soil texture and soil permeability) of each area of research that could potentially trigger flooding, 2) High level of flood hazards present in the study area with the Land Force (a) F1.Qal.I.pm.Al, (b) F1.Qal.I.Sw.Al, (c) F1.Qal.III.Kc.Lat, (d) F2.Qf.I.Kc.Lat, (e) F2.Qf.I.Pm.Al, (f) F2.Qf.I.Pm.Lat, (g) F2.Qf.I.SwAl, (h) F2.Qf.III.Ht.And, (i) V1.QTau.III.Pm.Lat, (j) V1.QTauIII.Pm.Lat, The study area has a moderate flood level of hazard present in the study area with land units (a) V1.QTau.III.Ht.Lat, (b) V1.QTau.III.Pm.Al, (c) V1.QTau.III.H.And. 3) The area of research that has a high level with a broad floods 486.58 Ha. And a research area with moderate flood hazard level has an area of ​​998.391 Ha.